Gaseous emission and ash characteristics from combustion of high ash content antibiotic mycelial residue in fluidized bed and the impact of additional water vapor. (15th August 2017) - Zhang, Guangyi; Liu, Huan; Ge, Yaxin; Gao, Shiqiu
Abstract: The gas (mainly NO and SO2 ) emission and ash characteristics from combustion of high ash content antibiotic mycelial residue (AMR) rich in N and S were investigated using a laboratory scale fluidized bed combustor, and the effects of addition of water vapor studied at the same time. The tested combustion temperature, excess air ratio (α) and mass ratios of water vapor-to-fuel (WV/F) varied in 750–950 °C, 1.3–1.9 and 0.4–1.4, respectively. Without additional water vapor present, both the concentrations of NO and SO2 in flue gas increased with elevating combustion temperature and excess air ratio, corresponding to the increases in conversion ratio of fuel-N to NO and emission ratio of S. The addition of water vapor facilitated excavating organic matters in the ash to result in its lower C and N contents. Additional water vapor formed partial reducing atmospheres, which were characterized by high CO and H2 concentrations in combustion atmosphere and low valence S in the ash, to thus visibly reduce NO. The SO2 concentration became slightly lower at the presence of additional water vapor and further decreased with more water vapor addition. Additional water vapor strengthened capture of SO2 by the ash. Higher WV/F ratios led to more porous structures in ash, accountable for NO reduction by catalytic effect as well as SO2 absorption. Nevertheless, it seems less possible to reduce NO and SO2 concentrations to meet their respective emission criteria, and other measures will thus have to be taken to control their emissions when directly combusting AMR for energy recovery.